To control and to be controlled: understanding the Arabidopsis SLIM1 function in sulfur deficiency through comprehensive investigation of the EIL protein family - Wawrzyńska, Anna; Sirko, Agnieszka (Frontiers in Plant Science, 2014)
SSLIM1, a member of the EIN3-like (EIL) family of transcription factors in Arabidopsis, is the regulator of many sulfur-deficiency responsive genes. Among the five other proteins of the family, three regulate ethylene responses and two have unassigned functions. Contrary to the well-defined ethylene signaling, the pathway leading from sensing sulfate status to the activation of its acquisition via SLIM1 is completely unknown. SLIM1 binds to the 20 nt-long specific UPE-box sequence; however, it also recognizes the shorter TEIL sequence, unique for the whole EIL family. SLIM1 takes part in the upregulation and downregulation of various sulfur metabolism genes, but also it controls the degradation of glucosinolates under sulfur deficient conditions. Besides facilitating the increased flux through the sulfate assimilation pathway, SLIM1 induces microRNA395, specifically targeting ATP sulfurylases and a low-affinity sulfate transporter, SULTR2;1, thus affecting sulfate translocation to the shoot. Here, we briefly review the identification, structural characteristics and molecular function of SLIM1 from the perspective of the whole EIL protein family.